NOTES ON THE GENUS CYLINDROCLADIUM (Fungi: Mucedinaceae) - BOEDIJN, K. B.; REITSMA, J. (REINWARDTIA, 1950)
The genus Cylindrocladivm was erected by Morgan in 1892 for a Mucedinaceous fungus with Penicillium-like branching and long,cylindrical,two-celled conidia.The original diagnosis runs: â Cylindrocladium Morgan. "Hyphae steriles repentes,fertiles erectae,dichoto mice ramosae,septatae, basidia in apice ramorum subterna fusoidea,conidia cylin- dracea, 1-septata." The type and only species,Cylindrocladium scoparium Morgan,was found on dead pods of Gleditschia triacanthos L.In 1900 the same fungus was reported by Ellis and Everhart on dead leaves of Asimina triloba Dun.They considered it a new species of the genus Diplocladhim Bonord.and described it accordingly as Diplocladium cylindrosporum Ell.& Everh.In 1912 Hawley (see Rea and Hawley) erected the genus Candelospora with the following diagnosis